2018
DOI: 10.1051/matecconf/201816202021
|View full text |Cite
|
Sign up to set email alerts
|

The role of ambient temperature variation on drying shrinkage development of self-compacting Portland-limestone cement concrete

Abstract: The ambient temperature records in Iraq show a large variation between day and night reaching 20 C, depending on the season, whether it is summer or winter. For this reason, the aim of this research is to study the effect of these conditions on the drying shrinkage of self-compacting concrete produced by using Portland-Limestone cement (ASTM C595 - Type IL). SCC mixes were designed to attain compressive strengths of 40 and 60MPa at 28days with and without silica fume respectively. Same mixes were reproduced wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Large diferences in relative shrinkage for diferent mixes at early ages, less than 28 days, were revealed by Al-Attar [4]. Al-Rihimy et al [5] declared that the Iraqi ambient temperature displays a large variation between day and night reaching 20 °C depending on the season, whether it is winter or summer. For this purpose, they studied the efect of these conditions on the drying shrinkage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Large diferences in relative shrinkage for diferent mixes at early ages, less than 28 days, were revealed by Al-Attar [4]. Al-Rihimy et al [5] declared that the Iraqi ambient temperature displays a large variation between day and night reaching 20 °C depending on the season, whether it is winter or summer. For this purpose, they studied the efect of these conditions on the drying shrinkage.…”
Section: Introductionmentioning
confidence: 99%
“…Te drying shrinkage is measured for 6 months after 7 days in water curing, for outdoor ambient temperature varies from −4 to +39 °C and the relative humidity ranges from 15 to 60%; results were compared to those of specimens kept in the shrinkage chamber, under controlled temperature of 21 °C and relative humidity of 35%. It was concluded that, due to the irreversible nature of shrinkage strain, the drop in ambient temperature and the rise of atmosphere moisture or relative humidity would not reverse the shrinkage strain [5]. Moreover, higher cement content in ECC results in a higher shrinkage magnitude.…”
Section: Introductionmentioning
confidence: 99%
“…This does not reflect the temperature on earth even in the tropics. The role of ambient temperature variation on drying shrinkage has been studied [2]. Environmentdependent creep tends to compensate for an increase in temperature strain [3].…”
Section: Introductionmentioning
confidence: 99%